2006
DOI: 10.1116/1.2232456
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical properties of ZnO–ZnS core-shell nanotube arrays

Abstract: Heterostructured ZnO-ZnS core-shell nanotube arrays with the diameters of 50-80 nm and lengths up to 1 m were synthesized by a two-step chemical reaction. First, the ZnO layer was grown by atomic-layer deposition. It was found that the preferred growth orientation was strongly dependent on the substrate temperature. After sulfuration conversion from arrayed ZnO nanorods, the ZnS-ZnO composite arrays can be successfully prepared, as evidenced from transmission electron microscopy. This confirms that the ZnO-ZnS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
(15 reference statements)
1
21
0
Order By: Relevance
“…Qualitatively, the effect of a ZnS coating is similar to that of a ZnSe coating reported previously. 15 It was recently reported that a ZnS coating over ZnO nanotubes or nanorods enhanced UV emission, 19,20 which appears to agree with conventional wisdom that ͑1͒ the coating of a large-band gap material diminishes the loss through surface recombination and ͑2͒ the UV emission is from the bulk part of the ZnO. However, this understanding is not expected to hold true for type II combinations such as ZnO/ZnS, even though ZnS has a larger band gap.…”
mentioning
confidence: 79%
“…Qualitatively, the effect of a ZnS coating is similar to that of a ZnSe coating reported previously. 15 It was recently reported that a ZnS coating over ZnO nanotubes or nanorods enhanced UV emission, 19,20 which appears to agree with conventional wisdom that ͑1͒ the coating of a large-band gap material diminishes the loss through surface recombination and ͑2͒ the UV emission is from the bulk part of the ZnO. However, this understanding is not expected to hold true for type II combinations such as ZnO/ZnS, even though ZnS has a larger band gap.…”
mentioning
confidence: 79%
“…5(b)). 18 Moreover, it can be Gaussian fitted to two peaks locating at 161.9 and 162.9 eV, which may arise from differential charging of the surface layer or some surface contamination (like residual Na 2 S) 12 …”
Section: Resultsmentioning
confidence: 99%
“…Typical examples of such nanostructures are the following: Integration of ZnO nanotubes with ordered nanorods, [227] conversion of ZnO nanorod arrays into ZnOÀZnS nanocable and ZnS nanotube arrays, [228] core-sheath heterostructure CdSÀTiO 2 nanotube arrays, [229] ZnS nanotube-In nanowire core-shell heterostructures, [230] ZnOÀZnS core-shall nanotube arrays, [231] Cu nanotube-Bi nanowire heterojunctions, [232] carbon nanotubes in TiO 2 nanotubes, [233] TiO 2 ÀPt coaxial nanotube arrays, [234] Sn nanowires on TiO 2 nanotubes, [235] Fe 2 O 3 ÀTiO 2 nanorod-nanotube arrays, [236] SiO 2 ÀTa 2 O 5 core-shell nanowires and nanotubes, [237] multi-walled BCN-carbon nanotube junctions, [238] and BN nanotubes with periodic iron nanoparticles. [239] …”
Section: Complex Inorganic Nanostructures Based On Nanotubesmentioning
confidence: 99%